From openness to restriction: South American governments’ responses to the Venezuelan exodus, 2014-2019 - Corrêa, Ugo Medrado (2019)
The Venezuelan exodus represents one of the most extensive political and humanitarian crises ever experienced in South America. Yet, governments in the region have failed to promote stability in Venezuela and have been unable to implement a coordinated response to the migration crisis across the subcontinent. By focusing on foreign and domestic action, I aim to better understand, beyond diplomatic discourse, what South American governments have done to deal with the spillovers of the Venezuelan collapse, and which factors have influenced their decision-making process. The present study offers a concept that identifies key attributes that constitute a facilitated immigration policy to Venezuelans. It is a pivotal step to provide tools for empirical analysis of the phenomenon. Then, I investigate which factors have influenced governments’ political response to the Venezuelan immigration crisis. Why president Evo Morales, Caracas’s close ally, did not facilitate immigration from Venezuela? Why the Brazilian president, Michel Temer, in turn, implemented an open-door policy for Venezuelan immigrants? This MSc thesis applies Qualitative Comparative Analysis (QCA) to the sample of nineteen South American governments from 2014 to 2019 — the epicenter of the Venezuelan exodus. Through QCA, I identify conditions shared by cases that have reached the same outcome — openness or restriction to Venezuelan immigration. Rightwing ideology has placed many South American presidents in strong opposition to the Maduro government. Thus, facilitating the arrival of Venezuelans immigrants on humanitarian grounds would instead send a powerful political message condemning the Bolivarian regime.